Disruption of c-MYC Binding and Chromosomal Looping Involving Genetic Variants Associated With Ankylosing Spondylitis Upstream of the RUNX3 Promoter - Cohen, Carla J.; Davidson, Connor; Selmi, Carlo; Bowness, Paul; Knight, Julian C.; Wordsworth, B. Paul; Vecellio, Matteo (Frontiers in Genetics, 2022)
Background:Ankylosing Spondylitis (AS) is a common inflammatory spinal arthritis with a complex aetiology and high heritability, involving more than100 genetic associations. These include several AS-associated single-nucleotide-polymorphisms (SNPs) upstream of RUNX3, which encodes the multifunctional RUNT-related-transcription-factor-(TF) 3. The lead-associated SNP rs6600247 (p=2.6x10-15) lies ~13kb upstream of the RUNX3 promoter adjacent to a c-MYC TF binding-site. The effect of rs6600247 genotype on DNA-binding and chromosome looping were investigated by EMSA, WEMSA and Chromosome Conformation Capture (3C). Results:Interrogation of ENCODE published data showed open chromatin in the region overlapping rs6600247 in primary human CD14+ monocytes, in contrast to primary human T-cells. The rs6600247 AS-risk allele is predicted to specifically disrupt a c-MYC binding-site. Using a 50bp DNAprobe spanning rs6600247 we consistently observed reduced binding to the AS-risk “C”allele of both purified c-MYC protein and nuclear extracts (NE) from monocyte-like U937 cells. WEMSA on U937 NE and purified c-MYC protein confirmed these differences (n=3; p<0.05). 3C experiments demonstrated negligible interaction between the region encompassing rs6600247 and the RUNX3 promoter. A stronger interaction frequency was demonstrated between the RUNX3 promoter and the previously characterised AS-associated SNP rs4648889. Conclusions:The lead SNP rs6600247, located upstream of the RUNX3 promoter, modulates c-MYC binding, but rs6600247 has rather limited physical interaction with the promoter of RUNX3. In contrast a clear chromatin looping event between the region encompassing rs4648889 and the RUNX3 promoter was observed. These data provide further evidence for complexity in the regulatory elements upstream of the RUNX3 promoter and the involvement of RUNX3 transcriptional regulation in AS.